A study of the relationship between the quality of lifestyle counselling and later adherence to the lifestyle changes based on patients with stroke and TIA. (April 2018) - Oikarinen, Anne; Engblom, Janne; Kyngäs, Helvi; Kääriäinen, Maria
Objective: To identify associations between lifestyle counselling quality and adherence to lifestyle changes during the 12-month period after discharge. Setting: Neurology unit. Subjects: Stroke and transient ischaemic attack (TIA) patients ( n = 98). Design: Longitudinal explorative study that utilized data initially collected for quasi-experimental study. Main measures: The exploratory measures of Counselling Quality were collected at the hospital on the day of discharge between January 2010 and October 2011, and the outcome measures of Adherence to Lifestyle Change and clinical values were collected 3, 6 and 12 months after discharge. Results: There were significant associations between the exploratory and outcome measures over time. Three of the counselling quality parameters, counselling interaction, advantages and resources, were found to be significantly associated with adherence to lifestyle change. In particular, counselling interactiveness was positively associated with physical activity at 3 ( B = 0.31, SD = 0.10, P = 0.004) and 12 ( B = 0.29, SD = 0.13, P = 0.030) months, as was advantages of following the advice at 3 ( B = 0.33, SD = 0.11, P = 0.006) and 12 ( B = 0.34, SD = 0.14, P = 0.021) months. Counselling resources were associated with lower body mass index throughout the entire follow-up period, that is, at 3 ( B = −0.06, SD = 0.02, P = 0.006), 6 ( B = −0.05, SD = 0.02, P = 0.040) and 12 months ( B = −0.05, SD = 0.02, P = 0.022). Furthermore, all aspects of counselling quality were positively related to support from nurses. Conclusion: Adherence to lifestyle change is more likely to be attained if lifestyle counselling is interactive, the advantages of following the given advice are perceived as beneficial and the counsellor has sufficient resources.